Phát minh sáng chế tại Việt Nam: Bằng chứng từ dữ liệu Orbis IP (1903–2023) - Dương Tuấn , Kiệt; Đặng Duy Khánh , Hoàng; Huỳnh Lưu Đức, Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
Using Orbis Intellectual Property data for 1903–2023, this paper provides descriptive data about long-run patenting activities in Vietnam and examines correlates of examination duration and technological impact. Patenting rises sharply from the late 1990s, while the mean filing-to-grant time is about 1,156 days and varies significantly across WIPO technology fields. Forward citations are highly right-skewed, with most patents uncited but a small fraction highly influential. Regressions with technology-field and patent-office fixed effects show that utility models are processed faster but receive fewer forward citations, whereas broader and more detailed protection, proxied by the number of claims, is positively associated with citations. The results imply that policies should prioritize examination efficiency and application quality to enhance the diffusion and commercialization of innovation in Vietnam